2019
DOI: 10.3390/biology8020044
|View full text |Cite
|
Sign up to set email alerts
|

N-acetyl-L-cysteine Prevents Lactate-Mediated PGC1-alpha Expression in C2C12 Myotubes

Abstract: Background: Exercise induces many physiological adaptations. Recently, it has been proposed that some of these adaptations are induced by exercise-mediated lactate production. In this study, we aimed to investigate in vitro the effect of lactate in cultured myotubes and whether antioxidants could inhibit the effect. Methods: Differentiated myotubes were cultured at different concentrations of L-lactate (0, 10, 30, 50 mM) in the absence or presence of an antioxidant, N-acetyl-L-cysteine (Nac). The temporal effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The results showed that ROS might act as mediators of lactate effect on autophagy. These results agree with previous studies in which ROS mediated the lactate up-regulation of PGC1-α in C2C12 (Nalbandian et al 2019), p38-MAPK signaling pathways in germ (Galardo et al 2014), and IL-8 expression in HUVEC cells (Végran et al 2011). ROS's nature mediating the autophagic effect of lactate in skeletal muscle cannot be determined from the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that ROS might act as mediators of lactate effect on autophagy. These results agree with previous studies in which ROS mediated the lactate up-regulation of PGC1-α in C2C12 (Nalbandian et al 2019), p38-MAPK signaling pathways in germ (Galardo et al 2014), and IL-8 expression in HUVEC cells (Végran et al 2011). ROS's nature mediating the autophagic effect of lactate in skeletal muscle cannot be determined from the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The idea of lactate being a signaling molecule has been tested in several models. In differentiated C2C12 cells (mouse immortalized myoblasts), culture with L-lactate increased the expression of PGC1-alpha (peroxisome proliferatoractivated receptor gamma coactivator 1-alpha), which is a transcription factor responsible for mitochondrial biogenesis (Nalbandian et al, 2019). Similarly, in differentiated L6 cells (immortalized rat myoblasts), culture with lactate increased the expression of PGC1-alpha as well as the expression of several genes related to metabolism like MCT1 (Hashimoto et al, 2007).…”
Section: A B Cmentioning
confidence: 99%
“…Moreover, treatment with allopurinol, an XO inhibitor, prevented the increase of PGC-1α and its target genes in the vastus lateralis muscle of rats after a single session of anaerobic exercise [ 102 ]. Lactate can stimulate mitochondrial biogenesis in cardiac and skeletal muscle [ 103 ], and recently, lactate-induced PGC-1α was shown to be blocked by antioxidant treatment, in C2C12 skeletal muscle cells [ 104 ], suggesting that a ROS can couple with lactate metabolism to stimulate PGC-1α production.…”
Section: The Role Of Ros In Physical Exercise Adaptationsmentioning
confidence: 99%